2014
DOI: 10.3109/14767058.2014.908179
|View full text |Cite
|
Sign up to set email alerts
|

Cervical fluid IL-6 and IL-8 levels in pregnancies complicated by preterm prelabor rupture of membranes

Abstract: The presence of MIAC is the most important factor impacting the local cervical inflammatory response, which is determined by IL-6 and IL-8 levels in the cervical fluid. IL-8 levels seem to be a promising non-invasive marker for the prediction of pregnancies complicated by the presence of both MIAC and HCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
2
34
0
1
Order By: Relevance
“…Spontaneous miscarriages have also been found to be associated with higher first and second trimester IL‐6 levels, showing an increased rate of miscarriages in pregnant women with IL‐6 levels above 1.725 pg/mL . Additionally, consistent with our results, previous studies have shown a relationship between PPROM and increased IL‐6 levels in maternal serum and cervicovaginal fluid during 24‐37 th weeks of gestation, as well as increased IL‐6 levels in the serum of IUGR neonates when compared with controls …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Spontaneous miscarriages have also been found to be associated with higher first and second trimester IL‐6 levels, showing an increased rate of miscarriages in pregnant women with IL‐6 levels above 1.725 pg/mL . Additionally, consistent with our results, previous studies have shown a relationship between PPROM and increased IL‐6 levels in maternal serum and cervicovaginal fluid during 24‐37 th weeks of gestation, as well as increased IL‐6 levels in the serum of IUGR neonates when compared with controls …”
Section: Discussionsupporting
confidence: 91%
“…suggested that IL‐6 might be a crucial factor in the maternal host response as a result of significantly higher levels of IL‐6 in patients with second trimester abortion . As systemic inflammation has been proposed to be responsible for preterm delivery (PTD) and the preterm premature rupture of membranes (PPROM), various cytokines, including IL‐6, have been already studied in different specimens, such as maternal plasma/serum, cervicovaginal and amniotic fluid, and has been found to be both associated and predictive for these adverse pregnancy outcomes . In autoimmune diseases, including Grave's disease, the role of antibodies is known to be T‐cell mediated .…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms may gain access to the amniotic cavity in patients with intact membranes, and induce an inflammatory response leading to the production of cytokines [73,75,76,81, [89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107], chemokines [108][109][110][111][112][113][114], other inflammatory mediators [115][116][117][118][119][120][121][122][123][124], and thrombin [125][126][127][128][129][130]. Microorganisms and their products can also induce the production of matrix degrading enzymes [65,[131][132][133][134][135]…”
Section: The Importance Of Microbial Invasion Of the Amniotic Cavity mentioning
confidence: 99%
“…82 The presence of intra-amniotic inflammation (both microbial and sterile) is associated with adverse pregnancy outcomes 35,8391 in patients presenting with preterm labor and intact membranes, 92–108 preterm pre-labor rupture of the membranes (PPROM), 109114 a sonographic short cervix, 60,62,82,115 and cervical insufficiency. 58,59,64,116,117 Thus, we and others have explored the behavior of cytokines and other inflammatory-related markers in amniotic 82,100,106108,118128 or vaginal 129140 fluid.…”
Section: | Introductionmentioning
confidence: 99%